Human CD36hi monocytes induce Foxp3+ CD25+ T cells with regulatory functions from CD4 and CD8 subsets. Issue 3 (7th March 2021) - Lee, Jessica G.; Jaeger, Kathleen E.; Seki, Yoichi; Wei Lim, Yi; Cunha, Christina; Vuchkovska, Aleksandra; Nelson, Alexander J.; Nikolai, Anya; Kim, Dan; Nishimura, Michael; Knight, Katherine L.; White, Paula; et al.
Summary: The fetal and neonatal immune systems are uniquely poised to generate tolerance to self, maternal and environmental antigens encountered in the womb and shortly after birth. However, the tolerogenic nature of fetal and neonatal immunity can be detrimental in the context of pathogens, leading to overwhelming bacterial infections or chronic viral infections. A variety of mechanisms contribute to fetal and neonatal tolerance, including a propensity to generate Foxp3 + regulatory T cells (Treg cells). However, the mechanism(s) of fetal Foxp3 + T‐cell differentiation, the specific antigen‐presenting cells required and factors that inhibit Treg generation after the neonatal period are poorly understood. Here, we demonstrate that a subset of CD14 + monocytes expressing the scavenger molecule, CD36, can generate CD4 + and CD8 + T cells that coexpress Foxp3 and T‐bet from both umbilical cord blood. These Foxp3 + T‐bet + T cells potently suppress T‐cell proliferation and ameliorate xenogeneic graft‐versus‐host disease. CD14 + CD36 + monocytes provide known Treg‐inducing signals: membrane‐bound transforming growth factor‐beta and retinoic acid. Unexpectedly, adult peripheral blood monocytes are also capable of inducing Foxp3 + T cells from both cord blood and adult peripheral naïve T cells. The induction of Foxp3 + T cells in umbilical cord blood by monocytes was inhibited by the lymphoid fraction of adult peripheral blood cells. These studies highlight a novel immunoregulatory role of monocytes and suggest that antigen presentation by CD36 hi monocytes may contribute to the peripheral development of Foxp3 + T‐bet + T cells with regulatory functions in both neonates and adults. Abstract : Antigen receptor stimulation of human umbilical cord blood T cells promotes the development of Foxp3 + CD25 + T cells with regulatory functions. We found that CD14 + CD36 + monocytes are critical for the induction of Foxp3 + CD25 + T cells from both umbilical cord blood and adult peripheral naïve T cells. However, adult peripheral blood contains a lymphoid subset that dominantly blocks the development of Foxp3 + T cells from cord blood, suggesting that a subset of adult lymphocytes develop post‐birth that direct T‐cell responses towards Foxp3 ‐ effector cells.